2003
DOI: 10.1002/pd.674
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward prenatal diagnosis, termination of pregnancy, and reproduction by parents of children with nonsyndromic oral clefts in Argentina

Abstract: Most respondents do not perceive oral clefts as a severe condition. Parents would not choose to terminate the pregnancy over delivery of such an affected newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…The responses of mothers of children with clefts to the same question are similar to the results of a study conducted in Argentina by Wyszynski, Perandones, and Bennum[16] wherein most parents of children with a cleft strongly support the continuation of pregnancy as they felt that an oral cleft is not a serious condition requiring the termination of pregnancy and only 6.4% of 165 parents chose to terminate pregnancy. The reason for the continuation of pregnancy with a cleft child in Argentina is explained on the basis that most subjects in the study were Catholics and abortion is legally restricted in Argentina.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The responses of mothers of children with clefts to the same question are similar to the results of a study conducted in Argentina by Wyszynski, Perandones, and Bennum[16] wherein most parents of children with a cleft strongly support the continuation of pregnancy as they felt that an oral cleft is not a serious condition requiring the termination of pregnancy and only 6.4% of 165 parents chose to terminate pregnancy. The reason for the continuation of pregnancy with a cleft child in Argentina is explained on the basis that most subjects in the study were Catholics and abortion is legally restricted in Argentina.…”
Section: Discussionsupporting
confidence: 75%
“…[14] The elective termination of pregnancy for prenatal diagnosis of a non-syndromic oral cleft has been viewed differently across the world, the concerns being ethical, religious, and cultural differences among the population. [1516]…”
Section: Introductionmentioning
confidence: 99%
“…In this survey, more than half of the scholars believed that counseling regarding affected fetuses does not influence mothers into deciding for abortion. In some studies, it has been shown that when faced with an anomaly such as Down syndrome and aneuploidies in which a poor prognosis was expected, most of the couples independently decided to terminate the pregnancy, even if termination of pregnancy was not legally available in their countries [3, 6, 7, 9, 16, 28]. One study in the Netherlands stated that the decision process regarding the affected fetus was influenced most by the husband and much less by (health) caregivers or family and friends.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, prenatal screening estimates a woman’s risk of having an affected pregnancy [2]. On the basis of the knowledge gained through genetic counseling and prenatal screening and testing, couples can choose to continue with the pregnancy and receive prenatal treatment, if available, or to terminate the pregnancy [1, 3]. Decisions regarding these issues are complex and depend upon different factors such as the health care system, social-cultural background, ethical and religious beliefs, as well as the laws on abortion of the country [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is interesting to note that when parents are asked if they are satisfied to have only learned of the malformation at the child's birth 9 to 41% of parents, according to the literature, say they would have preferred to have been informed sooner. Still most of them asserted that they were satisfied that they only learned of their child's defect at the time of its birth 1,9,12,19 . A single study has shown that all parents would have preferred a prenatal diagnosis 4 .…”
Section: -1 -Pre-natal Diagnosesmentioning
confidence: 99%